Efficient Narrowband Direction of Arrival Estimation Based on a Combination of Uniform Linear/Shirvani-Akbari Arrays. (6th September 2012) - Shirvani Moghaddam, Shahriar; Akbari, Farida
Abstract : Uniform linear array (ULA) geometry does not perform well for direction of arrival (DOA) estimation at directions close to the array endfires. Shirvani and Akbari solved this problem by displacing two elements from both ends of the ULA to the top and/or bottom of the array axis. Shirvani-Akbari array (SAA) presents a considerable improvement in the DOA estimation of narrowband sources arriving at endfire directions in terms of DOA estimation accuracy and angular resolution. In this paper, all new proposed SAA configurations are modelled and also examined, numerically. In this paper, two well-known DOA estimation algorithms, multiple signal classification (MUSIC) and minimum variance distortionless response (MVDR), are used to evaluate the effectiveness of proposed arrays using total root mean square error (RMSE) criterion. In addition, two new scenarios are proposed which divide angular search to two parts, directions close to array endfires as well as middle angles. For middle angles, which belong to (- 70 ° ≤ θ ≤ 70 ° ), ULA is considered, and for endfire angles, the angles which belong to (- 90 ° ≤ θ ≤ - 70 ° ) and (70 ° ≤ θ ≤ 90 ° ), SAA is considered. Simulation results of new proposed scenarios for DOA estimation of narrowband signals show the better performance with lower computational load.